Minority Languages and Documentary Media: Representation, Translation and Power [Editorial] - Sills-Jones, Dafydd; Jones, Elin Haf Gruffudd (European Centre for Minority Issues, 2026)
[From first paragraph] The relationship between documentary media and minority languages is both politically significant and ethically complex. Documentary has long occupied a distinctive position within public culture as a form associated with testimony, representation, and the mediation of lived realities. Yet language within documentary is never neutral. The inclusion, exclusion, translation, or framing of language – and of languages – shapes not only how audiences understand a film, but also how communities, identities, and cultural authority are represented on screen.